Cultural Content Analysis of English Textbooks for Junior High School Entitled “Bahasa Inggris When English Rings A Bell” - Lasmita, Ritanti; Safnil Arsyad; Alamsyah Harahap (Journal of English for Specific Purposes in Indonesia, 2024)
The most essential element of English teaching is culture. The cultural content of the language education and learning process supports students to describe the language that exists in that culture. Cultural content is communicated through the textbook as essential in education and learning. So, culture content analysis is critical to selecting, developing, and effectively using the correct textbooks. This research aims to examine the types of cultures represented in textbooks, classify them into source, target, and international cultures (Cortazzi & Jin, 1999), and how the cultures of the classified textbooks are represented. It is to discover aesthetic, social, semantic, and practical senses (Adaskou, Britten & Fahsi, 1990). Researchers used descriptive qualitative methods. This research data is from the English textbook When English Rings for Junior High School. This data is cultural material gathered from all textbook readings, conversations, tasks, and images and converted in frequency. Two results were found in the textbook analysis. First are the results presented in the textbook entitled "When English Rings the Bell," which are source culture, target culture, and international culture. Secondly, the culture of both textbooks was represented primarily by pragmatic sensations compared to aesthetic, semantic, and sociological sensations. Therefore, there was an imbalance between the type of culture presented and how cultures were presented in the textbook.